Peningkatan Pemahaman dan Keterampilan Liturgis Umat Stasi St. Kristoforus Delawau Melalui Pelatihan dan Pendampingan Liturgi Berbasis Praktik - Marcella Hondo; Antonius P Sipahutar; Sergius Lay; Anisa Putri Hulu (Jurnal Magistra, 2025)
Liturgical activities are the center of the Church’s faith life and serve as the primary means of fostering the faith of Catholic communities. However, many parish outstation members still require guidance regarding the order of the Eucharistic Celebration, the roles of liturgical ministers, and the enrichment of liturgical music. This community service activity was carried out at St. Christopher Delawau Outstation, Christ the King Gido Parish, on Sunday, November 9, 2025, by the Dian Mandala Choir group. The purpose of this activity was to introduce the proper order of the Eucharistic Celebration, to socialize Latin Ordinarium songs, and to build a spirit of fraternity in faith. The methods used included the Eucharistic Celebration, liturgical practice, choir training, demonstrations of liturgical duties, and fraternal interaction. The results of the activity indicated improved understanding among the faithful regarding the Eucharistic Celebration, enhanced skills in liturgical ministries (conductor, lector, psalmist, homilist), and the development of emotional closeness as fellow believers. This community service demonstrates that practice-based and dialogical approaches have a positive impact on strengthening the quality of liturgy among outstation communities.